A GIANT CAVERNOUS HEMANGIOMA OF THE HEART - M. A. Nechaenko; D. N. Fedorov; Yu. V. Frolova; A. S. Dzemeshkevich; O. A. Fokina; A. V. Dombrovakaya; S. L. Dzemeshkevich (Российский кардиологический журнал, 2015)
Aim. To demonstrate a clinical case of giant cavernous hemangioma of the heart.Material and methods. The operation was done:  resection of cavernous hemangioma of the right chambers of the heart and right atrium plastics with xenopericardial patch, modeling of the right atrium-ventricular sulcus, sewing of the conditions of artificial circulation and cold pharmacological cardioplegia.Results. The cavernous hemangioma of the heart was removed.Conclusion. The possibility of radical hemangioma removal was demonstrated,with good outcomes.